Examining family processes linked to adolescent problem behaviors in single-mother families: The moderating role of school connectedness - Lee, Woon Kyung; Joo, Young Sun (Frontiers in Psychology, 2022)
Objective: Previous research has shown that adolescents in single-mother households are at heightened risk for adjustment problems. However, limited studies have investigated the mechanisms leading to adolescent problem behaviors in single-mother households. To address this research gap, this study applied the Family Stress Model to examine how single mothers’ material hardship is linked to adolescent problem behaviors, focusing on the mediating roles of mothers’ depression and mother-adolescent closeness. The moderating role of adolescent school connectedness in the relationships between mother-adolescent closeness and school connectedness and between mothers’ depression and school connectedness was also investigated. Materials and Methods: The study analyzed data from 1,384 adolescents and their single mothers who participated in the Fragile Families and Child Wellbeing Study at Wave 6. The associations between study variables were analyzed using structural equation modeling by decomposing the direct, indirect, and total effects of material hardship on adolescent problem behaviors. School connectedness’s interactions with mother-adolescent closeness and mothers’ depression were also examined. Results: Results showed a significant indirect relationship between material hardship and adolescent problem behaviors through sequential mediation of mothers’ depression and mother-adolescent closeness. Mothers’ depression also significantly mediated the relationship between material hardship and problem behaviors. Lastly, school connectedness moderated the relationship between mother-adolescent closeness and adolescents’ internalizing behaviors. The association between mother-adolescent closeness and adolescents’ internalizing behavior was weaker for adolescents with higher levels of school connectedness. Conclusion: The results indicate the important indirect effect of economic strain on adolescents’ problems behaviors in single-mother households, which has been less emphasized compared to the effects in earlier childhood. High rates of material hardship and adolescent problem behaviors in single-mother families call for multifaceted interventions focusing on family processes and protective factors, including school environment.